Prevalence of internet addiction and its relation with depression, anxiety and stress in medical students of Pakistan. - Ahmad, Afaq; Hassan Rizvi, Ali; Uzair, Muhammad; Bashir, Humaira; Amin, Maria (Psychology, Health & Medicine, 2026)
Internet addiction (IA) is broadly defined as a non-chemical, behavioral addiction, which involves human-machine interaction, bringing in negative impacts in the person's mental and physical health equally and affecting his/her general wellbeing. The main aim of the study is to determine the prevalence of IA and its relation with depression, anxiety and stress in medical students. This is a cross-sectional study conducted using a self-administered questionnaire, from medical students all across Pakistan. The study sample was collected for a period of 3 months. The Young's Internet Addiction Test (YIAT20), consisting of 20 questions, and the Depression Anxiety Stress Scales (DASS21), consisting of 21 questions, were used. In total, 254 students filled the survey. The overall prevalence of Internet addiction was 67.7%. Our analysis showed that 43.3% of the respondents have mild, 22.4% have moderate and 2.0% have severe internet addiction. The odds ratio for internet addiction and depression is 1.98 (95% confidence level), the odds ratio for internet addiction and anxiety is 2.56 (95% confidence level) and the odds ratio for internet addiction and stress is 4.71 (95% confidence level). We conclude that the prevalence of internet addiction among undergraduate college students is strikingly high and co-relates to depression, anxiety, and stress. Internet addiction ought to be considered, among college students, reportable to the primary care doctors for better assessment of student and prevention of further mental health problems such as depression, anxiety, and stress.